PENGARUH KONFLIK DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT FASTRATA BUANA CABANG SERPONG TANGERANG SELATAN - Gabrile Gandy Meiseva; Shela Indah Savitri (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This research aims to determine the effect of work conflict and work environment on employee performance at PT Fastrata Buana, Serpong Branch. The research method used is a quantitative approach with an associative type of research. The population in this study consists of all employees of PT Fastrata Buana, Serpong Branch, totaling 38 people, with the sampling technique using saturated sampling, so the entire population was used as the research sample. Data were collected through the distribution of questionnaires. The data analysis techniques employed include validity test, reliability test, classical assumption test, multiple linear regression analysis, t-test (partial), F-test (simultaneous), and the coefficient of determination (R²) test using SPSS version 25. The results of this study indicate that work conflict has a negative and significant effect on employee performance, as evidenced by the value of t count = -3.251 < -t table = -2.030 and a significance value of 0.003 < 0.05. Furthermore, the work environment has a positive and significant effect on employee performance, with a t count = 5.487 > t table = 2.030 and a significance value of 0.000 < 0.05. Simultaneously, work conflict and work environment have a significant effect on employee performance, as shown by the F count = 18.726 > F table = 3.27 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) shows that the two independent variables contribute 50.1% to employee performance, while the remaining 49.9% is influenced by other factors outside this study.